The effectiveness of flow charts in improving the quality control of repair and construction work - Kustikova Yuliya Olegovna; Pankova Elena Valeryevna (E3S Web of Conferences, 2023)
Currently, improving the quality of repair-construction works is an important complex problem, insufficient attention to which inevitably leads to an increase in the cost of repair-construction works, an increase in operating costs, an increase in the number of current and overhaul repairs, as well as a decrease in the time between repairs, worsening the quality of life of consumers. In the worst cases, a low level of quality of repair and construction work can lead to accidents, become a source of threat to life and health, leading to accidents.